ANALISIS PENGARUH MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA PERUSAHAAN KOSMETIK DAN BARANG KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dahrani -; Nur Maslinda (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The purpose of this study was to analyze the effect of working capital on profitability (GPM, NPM, ROA, ROI, ROE dan EPS). Using a form of associative research approach. To see an overview of working capital in improving the profitability of the company. Source of data obtained by the secondary data while the data is the data type of documentation in the form of financial statements such as balance sheet and income statement and the cosmetics company household articles listed in the Indonesia Stock Exchange.Results of studies using testing PSAW Statistics 18, which shows the results of testing correlation Spearman with a significant = 0.05. The results of the acquisition of working capital against Gross Profit Margin (GPM) 0,248, Net Profit Margin (NPM) 0,262, Return On Asset (ROA) 0,214, Return On Investement (ROI) 0,152, Return On Equity (ROE) 0,031 and Earning Per Share (EPS) 0,458. This indicates that working capital has no significant effect on profitability (GPM, NPM, ROA, ROI, dan EPS), however working capital have a significant effect on ROE.